Nipah Virus: A Comprehensive Review (Asian Journal of Pharmaceutics (AJP), 2025)
The Nipah virus (NiV), an emerging zoonotic pathogen from the Henipavirus genus, is known to cause severerespiratory infections and encephalitis in humans. Since its first discovery in 1998 during an epidemic in Malaysia,NiV has repeatedly produced outbreaks in Bangladesh and India, often resulting in high fatality rates. Pteropusfruit bats serve as the primary natural reservoir for human transmission, which can occur through direct contact,contaminated food, or contact with diseased animals. Clinical symptoms vary widely, ranging from mild febrileillness to fatal encephalitis. Laboratory confirmation is achieved through molecular methods like reverse transcriptasepolymerase chain reaction and serological assays. Despite the lack of licensed treatments or vaccines, severaltherapeutic candidates such as ribavirin, favipiravir, monoclonal antibodies, and remdesivir have demonstratedvarying levels of efficacy in preclinical studies. Public health interventions, including surveillance, outbreakcontainment, and minimizing exposure to natural reservoirs, remain essential. Given its epidemic potential and lackof specific therapies, NiV has been designated a priority pathogen by the World Health Organization. Continuedresearch and coordinated global efforts are critical to develop effective prevention and management strategies